1999
DOI: 10.1023/a:1022342431514
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Patients with somatization disorder (SD) endorse high rates of psychiatric symptoms. However, prior studies have not addressed whether these endorsed symptoms reflect underlying psychiatric illness or whether they represent symptom overendorsement mirroring somatic complaints in patients with SD. Thirty-two female outpatients with SD and 101 with other psychiatric disorders completed a checklist of current and lifetime psychiatric symptoms. These findings were analyzed with respect to the diagnoses given by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…DeSouza and colleagues [ 95 ] reported that patients with somatization disorder had significantly greater numbers of depressive symptoms even than patients diagnosed with major depressive disorder. Consistent with this observation, North and her research team [ 59 ] found that patients with somatization disorder acknowledged significantly as many or more current and lifetime symptoms of other psychiatric disorders compared to patients with other psychiatric disorders but without somatization disorder, although almost none of the somatization disorder patients met diagnostic criteria for these other diagnoses. Patients in this study with cluster B personality disorders (predominantly borderline personality disorder) without somatization disorder also endorsed as many psychiatric symptoms of these other disorders as patients with somatization disorder, significantly more than patients with other Axis I psychiatric disorders.…”
Section: Extensive Phenomenological Overlap Of Dissociative Convementioning
confidence: 76%
See 2 more Smart Citations
“…DeSouza and colleagues [ 95 ] reported that patients with somatization disorder had significantly greater numbers of depressive symptoms even than patients diagnosed with major depressive disorder. Consistent with this observation, North and her research team [ 59 ] found that patients with somatization disorder acknowledged significantly as many or more current and lifetime symptoms of other psychiatric disorders compared to patients with other psychiatric disorders but without somatization disorder, although almost none of the somatization disorder patients met diagnostic criteria for these other diagnoses. Patients in this study with cluster B personality disorders (predominantly borderline personality disorder) without somatization disorder also endorsed as many psychiatric symptoms of these other disorders as patients with somatization disorder, significantly more than patients with other Axis I psychiatric disorders.…”
Section: Extensive Phenomenological Overlap Of Dissociative Convementioning
confidence: 76%
“…Psychoform symptoms from the Perley-Guze criteria for Briquet’s syndrome that were not included in DSM-III criteria for somatization disorder included anxiety (nervousness, fears), depressive (low mood, crying, hopelessness, suicidal ideation), and psychotic (hallucinations) symptoms [ 14 ]. The term “psychoform” as defined by North et al was subsequently applied by Wetzel, Guze, Cloninger, Martin, and Clayton [ 58 ] (p. 565) and has also appeared in several other academic publications [ 16 , 17 , 59 , 60 ].…”
Section: Dissociation Conversion and Hysteria In The American DImentioning
confidence: 99%
See 1 more Smart Citation
“…Ранее большое значение в развитии СР придавалось наличию истерических черт. В настоящее время получены результаты о роли преморбидного склада личности других типов (с преобладанием тревожных, сенситивных, шизоидных, пограничных и других черт), что не позволяет рассматривать истерические черты личности как единственные, характерные для больных СР (Чижова, 2012;Собенников, 2014;Прибытков, Юркова и Баженова, 2016;Tomenson et al, 2012;Lenze, Miller, & Munir, et al, 1999).…”
Section: медицинская психологияunclassified